PENGARUH MODAL INTELEKTUAL, ARUS KAS BEBAS DAN PERTUMBUHAN ASET TERHADAP NILAI PERUSAHAAN - Haniah Barmin; Erida Herlina (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Firm value is an investor's view of the success of a company which is usually rated by the stock price. The value of the firmvis very important, because it can reflect the firm's financial performance which can have an impact on the desire of investors to invest in the firm. The firm value can reflect how the condition of the company. The purpose of this study was to determine the effect of intellectual capital, free cash flow, asset growth, liquidity and business risk to firm value. The population of this study is LQ45 company that listed in Indonesia Stock Exchange from 2017 to 2019. The sampling method used was purposive sampling method with a sample size of 183 during the 3 year observation period. The analytical technique used in this research is multiple linear regression analysis with Statistical Package for Social Sciences (SPSS) Ver. 25. The results of this study indicate that the variable intellectual capital, free cash flow and asset growth do not significantly influence firm value while the liquidity and business risk variable has a significant positive effect on firm value.